Mesogenic Schiff Base with Bromo End Group: Synthesis and Thermotropic Properties - Ha, Sie-Tiong; Lee, Teck-Leong; Lin, Hong-Cheu; M. Ito, Masato; Abe, Kazuma; Kubo, Kenji; Sreehari Sastry, S. (Asian Journal of Chemistry, 2012)
A new homologous series of Schiff base esters comprising a terminal bromo substituent was studied. The bromo substituent contributes to the molecular polarizability, thus, affecting intermolecular interactions, hence, resulting in smectic polymorphism. The mesomorphic properties were studied using differential scanning calorimeter and polarizing optical microscope attached to a Linkam hotstage. Whilst the lower members, n-ethanoyloxy and n-butanoyloxy derivatives were non-mesogens, n-hexanoyloxy member exhibited monotropic (less stable) smectic A and smectic B phases. Further lengthening of the alkanoyloxy chain from C8 to C12 (medium members), led to formation of enantiotropic (more stable) smectic A and smectic B mesophases based on the observation of both phases during heating and cooling cycles. The high members of the series, C14, C16 and C18 exhibited enantiotropic smectic A phase and monotropic smectic B phase. The homologous members were compared with structurally related series to establish their chemical structure-mesomorphic behaviour relationships.